Challenges and perspectives on innovative technologies for biofuel production and sustainable environmental management. (1st October 2022) - Khan, Shamshad; Naushad, M.; Iqbal, Jibran; Bathula, Chinna; Al-Muhtaseb, Ala'a H.
Graphical abstract: Highlights: The sustainability of biofuel technologies is discussed in depth. Biofuels' present and future challenges and requirements are studied. Productivity and sustainability are improved by bioengineering. The production of biofuels from organic waste ensures sustainability. Abstract: Specifically, human activities, such as those in industry and transportation, have resulted in an increase in the demand for fossil fuels, resulting in severe environmental problems. Throughout this article, we discuss the potential and challenges associated with the production of biofuels from a variety of feedstocks and advances in processing technologies utilizing a range of feedstocks. Based on the conclusion of the study, we conclude that bioenergy is a green alternative to be used for diverse energy needs, once the appropriate conversion processes are applied. The production of biofuels and their use in industries and transportation have significantly reduced the use of fossil fuels. The literature review concluded that producing biofuels from energy crops and microalgae was the most efficient and attractive method. The purpose of this review is to explain all aspects of biofuels and their sustainability criteria. With a particular focus on the role of nanotechnology in biofuel production, this article discusses the most recent advances in biofuel production. A number of emerging techniques have been investigated for improving process quality, including integrated techniques, less energy-intensive distillation strategies, and the use of microorganisms in engineering. A challenging aspect of biofuel production on a large scale remains; therefore, a novel technology must be developed in order to enhance biofuel production in order to meet the challenges and meet future energy needs.